Fabrication of Thermal Intelligent Core/Shell Nanofibers by the Solution Coaxial Electrospinning Process. Issue 1 (23rd April 2015) - Rezaei, Babak; Ghani, Mozhdeh; Askari, Mohsen; Shoushtari, Ahmad Mousavi; Malek, Reza Mohammad Ali
ABSTRACT: In this study, the authors present a promising structure of shape‐stabilized phase change materials (PCMs) with remarkable thermal energy storage capacity as core/shell phase change nanofibers. In this regard, solutions of polyethylene glycol (PEG) (as an important category of PCMs) and cellulose acetate (CA) were used as core and shell solutions, respectively. Electrospinning with a coaxial spinneret was performed, and nanofibers with the mean diameter of 545 nm under the controlled condition were produced. The formation of the core/shell structure was verified by scanning electron microscopy, attenuated total reflection Fourier transform infrared spectroscopy, and transmission electron microscopy analyses. Moreover, thermogravimetric analysis results not only revealed the thermal stability improvement of PCM but also confirmed the presence of the core/shell structure too. Differential scanning calorimetry analysis was also performed to measure the thermal energy storage capacity of the core/shell phase change nanofibers before and after a thermal cyclic test. A major finding in the present study is that the thermal energy storage capacity of core/shell nanofibers after the thermal cyclic test is significantly higher (41.23 J/g) than initial one (14.77 J/g). Ultimately, it can be summarized that the special core/shell configuration provides desirable thermal stability and durability concurrently along with high thermal energy storage capacity.